2009
DOI: 10.1007/s00415-009-5282-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of functioning in multiple sclerosis using the ICF

Abstract: The objective of this study was to explore whether it is possible to describe based on the International Classification of Functioning, Disability and Health (ICF) relevant aspects of functioning and disability affected in multiple sclerosis (MS) as well as environmental factors relevant to persons with MS. The specific aim was to identify most relevant 'Body functions', 'Body structures', 'Activities and participation', as well as 'Environmental factors' in patients with MS using the ICF. Additionally, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 34 publications
3
81
0
3
Order By: Relevance
“…The SCQ determines if the co-morbidity limits activities and whether treatment is received. The SCQ has previously been used in a study of people with MS [32]. In our study, two arthritic co-morbidities were combined into one.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…The SCQ determines if the co-morbidity limits activities and whether treatment is received. The SCQ has previously been used in a study of people with MS [32]. In our study, two arthritic co-morbidities were combined into one.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…All these components are affected by interactions between health conditions and contextual factors, including personal and environmental influences. 31 Linking MS to ICF describes the whole health experience of MS patients and provides a uniform language and framework to describe MS-related health. 31 As such, patient activation in MS should include structured exercise to improve patient's activity/capacity as well as a behavioural change to improve patient's participation in daily life.…”
Section: Patient Activation In Self-management: the Opportunities Of mentioning
confidence: 99%
“…(2) The patient perspective was explored through a qualitative focus group study performed with 27 individuals with MS [20]. (3) The expert perspective was captured with an internet-based expert survey including 173 health professionals from 46 countries with at least 5 years of expertise in the treatment or rehabilitation of people with MS. (4) The clinical perspective was explored by a multicentre empirical study in Germany and Switzerland by applying ICF categories in 205 people with MS [21]. Based on the empirical study, 139 second-level categories were identified as candidate categories.…”
Section: Preparatory Studiesmentioning
confidence: 99%